Phase variation in the glycosyltransferase genes of Pasteurella multocida associated with outbreaks of fowl cholera on free-range layer farms. Issue 3 (10th March 2022) - Omaleki, Lida; Blackall, Patrick J.; Cuddihy, Thom; White, Rhys T.; Courtice, Jodi M.; Turni, Conny; Forde, Brian M.; Beatson, Scott A.
Abstract : Fowl cholera caused by Pasteurella multocida has re-emerged in Australian poultry production since the increasing adoption of free-range production systems. Currently, autogenous killed whole-cell vaccines prepared from the isolates previously obtained from each farm are the main preventative measures used. In this study, we use whole-genome sequencing and phylogenomic analysis to investigate outbreak dynamics, as well as monitoring and comparing the variations in the lipopolysaccharide (LPS) outer core biosynthesis loci of the outbreak and vaccine strains. In total, 73 isolates from two different free-range layer farms were included. Our genomic analysis revealed that all investigated isolates within the two farms (layer A and layer B) carried LPS type L3, albeit with a high degree of genetic diversity between them. Additionally, the isolates belonged to five different sequence types (STs), with isolates belonging to ST9 and ST20 being the most prevalent. The isolates carried ST-specific mutations within their LPS type L3 outer core biosynthesis loci, including frameshift mutations in the outer core heptosyltransferase gene ( htpE ) (ST7 and ST274) or galactosyltransferase gene ( gatG ) (ST20). The ST9 isolates could be separated into three groups based on their LPS outer core biosynthesis loci sequences, with evidence for potential phase variation mechanisms identified. The potential phase variation mechanisms included a tandem repeat insertion in natC and a single base deletion in a homopolymer region of gatG . Importantly, our results demonstrated that two of the three ST9 groups shared identical rep-PCR (repetitive extragenic palindromic PCR) patterns, while carrying differences in their LPS outer core biosynthesis loci region. In addition, we found that ST9 isolates either with or without the natC tandem repeat insertion were both associated with a single outbreak, which would indicate the importance of screening more than one isolate within an outbreak. Our results strongly suggest the need for a metagenomics culture-independent approach, as well as a genetic typing scheme for LPS, to ensure an appropriate vaccine strain with a matching predicted LPS structure is used.